1997
DOI: 10.1084/jem.186.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Basic Protein–specific T Helper 2 (Th2) Cells Cause Experimental Autoimmune Encephalomyelitis in Immunodeficient Hosts Rather than Protect Them from the Disease

Abstract: Chronic inflammatory autoimmune diseases such as multiple sclerosis, diabetes, and rheumatoid arthritis are caused by CD4+ Th1 cells. Because Th2 cells antagonize Th1 cell functions in several ways, it is believed that immune deviation towards Th2 can prevent or cure autoimmune diseases. Experimental autoimmune encephalomyelitis (EAE) is a demyelinating disease used as a model for multiple sclerosis. Using an adoptive transfer system we assessed the role of Th1 and Th2 cells in EAE. In vitro generated Th1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
221
0
4

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(232 citation statements)
references
References 41 publications
7
221
0
4
Order By: Relevance
“…Histologic sections of CNS or kidney tissue from Ag: IFA-injected animals were indistinguishable from those of naive mice, even up to 24 wk after the initial injection. We specifically did not see any evidence of eosinophilic infiltration that might be associated with type 2 immune responses (33)(34)(35). In our hands, therefore, the classic CFA/IFA paradigm holds with respect to disease induction for three models of EAE and for ␣TBM disease: immunization in CFA induces autoimmune disease, and injection in IFA does not.…”
Section: Injection Of Autoantigen In Cfa But Not In Ifa Induces Orgmentioning
confidence: 84%
See 1 more Smart Citation
“…Histologic sections of CNS or kidney tissue from Ag: IFA-injected animals were indistinguishable from those of naive mice, even up to 24 wk after the initial injection. We specifically did not see any evidence of eosinophilic infiltration that might be associated with type 2 immune responses (33)(34)(35). In our hands, therefore, the classic CFA/IFA paradigm holds with respect to disease induction for three models of EAE and for ␣TBM disease: immunization in CFA induces autoimmune disease, and injection in IFA does not.…”
Section: Injection Of Autoantigen In Cfa But Not In Ifa Induces Orgmentioning
confidence: 84%
“…This view has more recently come under significant scrutiny. It was shown, for example, that the cotransfer of autoreactive, Th2-polarized, putative regulatory T cells with Th1-polarized effector T cells did not prevent or ameliorate autoimmune pathology, even when the Th2 cells were in marked excess over the Th1 cells (33)(34)(35). To the contrary, such adoptive transfers indicated that the autoreactive Th2 cells could themselves induce inflammatory responses in the target organ, thus contributing to tissue destruction.…”
Section: Revisiting Tolerance Induced By Autoantigen In Incompletementioning
confidence: 99%
“…Many studies have implicated Th1 cells in pathogenesis of EAE (3)(4)(5)(6)(7). In a recent report, IL-17-producing Th17 cells have been suggested to be an important encephalitogenic T cell subset (8).…”
Section: Discussionmentioning
confidence: 99%
“…EAE shares many clinical and histopathological features with multiple sclerosis (MS) and is a commonly used animal model of this human autoimmune disease (1,2). EAE is believed to be a Th1-induced autoimmune disease because of the increased expression of Th1 cytokines in the affected CNS and because injection of myelin specific CD4 ϩ Th1 but not Th2 cells into immunocompetent mice is sufficient to induce EAE (3)(4)(5)(6)(7). More recently, IL-17-producing Th17 cells have been implicated in pathogenesis of EAE (8 -10).…”
Section: Il-23 Is Critical In the Induction But Not In The Effectormentioning
confidence: 99%
“…B10.PL wild-type (WT) mice were purchased from The Jackson Laboratory (Bar Harbor, ME). MBP-TCR transgenic mice [34] were a generous gift from Dr. J. Lafaille, and were reared in our animal facilities under specific pathogen-free conditions. NOD and B10.PL WT animals were housed in a conventional mouse facility.…”
Section: Animalsmentioning
confidence: 99%